Institutional Adaptation to Zoning-Based School Admission Policy: A Qualitative Case Study of a Public Senior High School - Paiman; Abdul Malik Ramadhan; Peti Alawiyah (Al-Qalam Institue, 2025)
This study aims to examine the implementation of a zoning-based school admission policy and its implications for institutional adaptation, leadership practices, and organizational management in public secondary education. The research employed a qualitative case study design. Data were collected through semi-structured interviews with school leaders, teachers, and administrative staff, complemented by observations and document analysis. The data were analyzed using thematic analysis, including coding, categorization, and synthesis to identify patterns of institutional adaptation. The findings reveal three major themes: (1) institutional adaptation through organizational restructuring and strategic leadership, (2) instructional adjustments to address increasingly diverse student characteristics, and (3) stakeholder engagement to sustain institutional legitimacy and public trust. Leadership played a pivotal role in coordinating adaptive strategies, strengthening internal management, and ensuring policy compliance while maintaining educational quality. The study concludes that zoning policy implementation represents a multidimensional institutional transformation process rather than merely an administrative admission mechanism. The findings provide theoretical contributions to the literature on educational policy implementation and offer practical implications for policymakers and school leaders seeking to enhance institutional capacity and promote sustainable educational equity.